2001
DOI: 10.1007/s005200000233
|View full text |Cite
|
Sign up to set email alerts
|

Difference in patient's acceptance of early versus late initiation of psychosocial support in breast cancer

Abstract: The present study was performed to assess the difference in acceptance of psychosocial counseling and resulting benefits between patients with breast cancer with early or late onset. In a prospective randomized controlled study conducted over 6 months, 41 women with a new diagnosis of early breast cancer (group 1) and 43 patients with advanced breast cancer (group 2) received individually tailored psychosocial support and were compared against controls. This therapy was free of charge, and the duration of supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 21 publications
2
35
2
1
Order By: Relevance
“…It appeared that 22 studies did not meet the inclusion criteria as described (Table 3). Five studies (Connor, 1992;Corner et al, 1996;Scholten et al, 2001;Giese-Davis et al, 2002;Sloman, 2002) met the inclusion criteria and were included in the systematic review. An additional five studies (Arathuzik, 1994;Bredin et al, 1999;Edelman et al, 1999;Classen et al, 2001;Goodwin et al, 2001) that met the criteria for inclusion were identified by checking the references of located, relevant papers and searching for studies that have cited these papers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It appeared that 22 studies did not meet the inclusion criteria as described (Table 3). Five studies (Connor, 1992;Corner et al, 1996;Scholten et al, 2001;Giese-Davis et al, 2002;Sloman, 2002) met the inclusion criteria and were included in the systematic review. An additional five studies (Arathuzik, 1994;Bredin et al, 1999;Edelman et al, 1999;Classen et al, 2001;Goodwin et al, 2001) that met the criteria for inclusion were identified by checking the references of located, relevant papers and searching for studies that have cited these papers.…”
Section: Resultsmentioning
confidence: 99%
“…However, behaviour therapy was used in 12 trials, including one or more of the following: relaxation exercises, guided imagery, visualisation or cognitive approaches focusing on changing specific thoughts or beliefs and learning specific coping skills. In six (Arathuzik, 1994;Scholten et al, 2001;Sloman, 2002) of these 12 trials, behaviour therapy was used as a single intervention. A combined intervention of behaviour therapy and group support was used in four trials (Edelman et al, 1999;Goodwin et al, 2001;Classen et al, 2001;Giese-Davis et al, 2002).…”
Section: Description Of Included Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent studies with breast cancer patients have shown mixed or negative results. (Edelman et al, 1999;Edmonds et al, 1999;Scholten et al, 2001;Owen et al, 2005). However, none of these trials used a specialised breast nurse.…”
Section: Previous Research On Psycho-educational Interventions With Pmentioning
confidence: 99%
“…However, even in cancer settings, not all patients want help with their problems and this may be especially so in relation to psychosocial difficulties. For example, Scholten et al (2001) found that only 40% of 43 women with advanced breast cancer were willing to accept psychological counselling [4]. In a large Canadian sample of 2776 patients, almost 50% of those who met criteria for distress had neither sought professional psychosocial support and nor intended to do so in the future [5].…”
Section: Introductionmentioning
confidence: 99%